Heteroquely, laterality, maturity body size and shape variation of males and females of the endemic South American anomuran Aegla quilombola Moraes, Tavares & Bueno, 2017. Issue 1 (2nd January 2021) - da Silva, Alexandre R.; Lemes, Luiz Gustavo Mendes; Nogueira, Caio Santos; Bispo, Pitágoras C.; Castilho, Antonio Leão
ABSTRACT: Aegla quilombola is an anomuran crab endemic to São Paulo State, Brazil. The present manuscript aims to provide information about sexual dimorphism using geometric morphometrics, as well as information about heterochely, laterality and sexual maturity. The specimens were sampled in Intervales State Park. The carapace and chelipeds of all animals were photographed and landmarks digitalized. In the analyses, the propodus of the first pair of pereopods (chelipeds) were used. The same structures were measured for morphometric sexual maturity, analysing the relationships between carapace length (CL) x propodus height for males, and CL x abdomen length (ABL) for females. For heterochely and laterality, the height of male and female chelipeds were evaluated. Morphological differences were found in the shape of the posterior margin of the carapace and in the chelipeds' palmar region. Males reached morphometric maturity at smaller sizes and showed heterochely and laterality, usually having a larger left cheliped. These differences are probably related to differential energy use by males and females in fulfiling specific ecological roles. Females had larger abdominal margins to invest in reproduction and males invested energy in chelipeds that were more robust and larger than females, as chelipeds are often used in agonistic interactions and to obtain better resources.